Performance Framework for Parliamentary Finance, Budget, and Public Accounts Committees in the Western Balkans - World Bank (World Bank, Washington, DC, 2020)
The World Bank has been collaborating with parliamentary finance, budget, and public accounts committees in the Western Balkans as part of a knowledge partnership focusing on strengthening financial oversight practices. Many parliaments recognize the critical role they play approving the budget and ensuring it achieves its stated goals in an efficient and effective manner consistent with parliament’s appropriations. A gap persists between the international standards that touch upon the role of the parliament in the budget process - which have been developed by the global public finance community - and parliamentary assessment frameworks that speak to the performance of parliament, generally. The World Bank used international financial management standards and parliamentary assessment frameworks as the starting point for a multi-year initiative aimed at distilling and building consensus around financial oversight practices, reforms, successes, and challenges within the Western Balkans.